Snow White : a mirroring of reality in the reel world - Tan, Aaron Justin Li Jie (2013)
In the tale of Snow White, ‘once upon a time’ and ‘happily ever after’ are words that signify the beginning and the end of the magical journey of the fairy tale. However, this idea of the ‘happily ever after’ is arbitrary. For, like Snow White, each person is perpetually changing, and there is this requirement for stories to offer some instruction as well. Snow White has archetypal symbols such as the beautiful princess, the gallant hero and the wicked stepmother, which are reworked and re-imagined to align with societal values and expectations accordingly. However, one enduring trait of Snow White would be the perennial feminine beauty ideal; the connection between intrinsic and extrinsic beauty is also highlighted to emphasize that beauty is not a mere state of physicality, but a physical manifestation of beauty as a result of her inner beauty such as virtues and goodness of self. I will be discussing the development of Snow White as a character, which can be traced through the exploration of the original Brother’s Grimm Tale and three other film adaptations of Snow White, revealing the progression/regression of the character in an attempt to show the mirroring of real life through the ever-evolving depiction of Snow White.